2016
DOI: 10.1111/aas.12779
|View full text |Cite
|
Sign up to set email alerts
|

No convincing association between post‐operative delirium and post‐operative cognitive dysfunction: a secondary analysis

Abstract: There is no clear evidence that postoperative delirium is independently associated with POCD up to 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 31 publications
1
25
0
1
Order By: Relevance
“…60,61 Others have also reported associations between postoperative delirium and postoperative cognitive dysfunction at hospital discharge or 1 month, but not at later follow-up. 9,57,58 Franck et al 54 only found an association between postoperative delirium and postoperative cognitive dysfunction in a subgroup of participants, and concluded that there was no clear evidence that delirium is independently associated with postoperative cognitive dysfunction beyond 1 week after surgery. Our findings support those of others that suggest a link between postoperative delirium and postoperative cognitive dysfunction in early recovery.…”
Section: Discussionmentioning
confidence: 99%
“…60,61 Others have also reported associations between postoperative delirium and postoperative cognitive dysfunction at hospital discharge or 1 month, but not at later follow-up. 9,57,58 Franck et al 54 only found an association between postoperative delirium and postoperative cognitive dysfunction in a subgroup of participants, and concluded that there was no clear evidence that delirium is independently associated with postoperative cognitive dysfunction beyond 1 week after surgery. Our findings support those of others that suggest a link between postoperative delirium and postoperative cognitive dysfunction in early recovery.…”
Section: Discussionmentioning
confidence: 99%
“…1 In some severe cases, it will induce the decline or loss of work ability and activities of daily living in patients. 3 The incidence within 1 week and 3 months after surgery are as high as 47.3% and 6.3%, respectively. 2 Previous study have suggested that POCD frequently occurs after major operations, such as coronary artery bypass grafting and orthopedic operation.…”
Section: Introductionmentioning
confidence: 98%
“…2 Previous study have suggested that POCD frequently occurs after major operations, such as coronary artery bypass grafting and orthopedic operation. 3,4 Generally, surgery will induce systemic inflammation. 1 However, the precise mechanism of action of POCD remains unclear at present, and the aged patients have more severe POCD.…”
Section: Introductionmentioning
confidence: 99%
“…There remains an interesting issue of the relationship between delirium and POCD; some have suggested an increase in POCD with those experiencing delirium [15,16], whilst others have asserted that no such relationship exits [17].…”
mentioning
confidence: 99%